2004
DOI: 10.2460/ajvr.2004.65.616
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of serum values of pancreatic enzymes after endoscopic retrograde pancreatography in dogs

Abstract: Results indicated that ERP appears to be a safe imaging technique of pancreatic ducts in healthy dogs, although it induced a transient increase in serum values of pancreatic enzymes. In dogs, repeated clinical examinations and serum enzyme determinations can be used to monitor ERP-induced complications such as acute pancreatitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 12 publications
3
20
0
Order By: Relevance
“…However, a later publication from the same authors also reported a wideranging baseline cPE-1 concentration in 7 healthy dogs (0.1-411.6 ng/ml) but with a median value of 5.5 ng/ml, similar to the dogs with non-pancreatic disease in the present study. 15 This initially wide reference interval raises the question of whether sample handling or hemolysis may have contributed to the variability of measured values. The manufacturers of the assay report that hemolysis or storage above 8°C for more than 72 hr can artifactually increase serum cPE-1 measurements.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, a later publication from the same authors also reported a wideranging baseline cPE-1 concentration in 7 healthy dogs (0.1-411.6 ng/ml) but with a median value of 5.5 ng/ml, similar to the dogs with non-pancreatic disease in the present study. 15 This initially wide reference interval raises the question of whether sample handling or hemolysis may have contributed to the variability of measured values. The manufacturers of the assay report that hemolysis or storage above 8°C for more than 72 hr can artifactually increase serum cPE-1 measurements.…”
Section: Discussionmentioning
confidence: 99%
“…15 An earlier abstract of 16 healthy dogs had a minimum value of 32.1 ng/ml, and a maximum value of 659.3 ng/ml, with a median concentration of 55.8 ng/ml (Spillmann et al, J Vet Intern Med abstract 2002; 16:635). Unfortunately, the mean values were not reported in that study.…”
Section: Animal Selectionmentioning
confidence: 99%
See 2 more Smart Citations
“…43 A further study from the same investigators assessed the measurement of serum cPE-1, along with amylase, lipase, and TLI in 7 healthy beagles after endoscopic retrograde pancreatography, a procedure that is commonly associated with the development of pancreatic inflammation. 44 There was no difference between the baseline and any subsequent measurement of cPE-1 in any dog, although there was in the other 3 enzymes. Additionally, the range at baseline for the 7 healthy dogs was quite wide (0.1-411.6 ng/mL) with a median of 5.5 ng/mL.…”
Section: Box 2 Case Studymentioning
confidence: 87%